Peronism as a big tent the political inclusion of Arab immigrants in Argentina - Rain, Raʿanan 1960-; Noyjovich, Ariel (McGill-Queen's University Press, 2022)
"Argentina's populist movement, led by Juan Perón, welcomed people from a broad range of cultural backgrounds to join its ranks. Unlike most populist movements in Europe and North America, Peronism was of an inclusive nature, rejecting racism and xenophobia. In Peronism as a Big Tent Raanan Rein and Ariel Noyjovich examine Peronism's attempts at garnering the support of Argentines of Middle Eastern origins--be they Jewish, Maronite, Orthodox Catholic, Druze, or Muslim--in both Buenos Aires and the interior provinces. By following the process that started with Perón's administration in the mid-1940s and culminated with the 1989 election of President Carlos Menem, of Syrian parentage, Rein and Noyjovich paint a nuanced picture of Argentina's journey from failed attempts to build a mosque in Buenos Aires in 1950 to the inauguration of the King Fahd Islamic Cultural Center in the nation's capital in the year 2000. Peronism as a Big Tent reflects on Perón's own evolution, from perceiving Argentina as a Catholic country with little room for those outside the faith to embracing a vision of a society that was multicultural and that welcomed and celebrated religious plurality. The legacy of this spirit of inclusiveness can still be felt today."--
Translation of: Los muchachos peronistas árabes
Keywords: Geschichte 1945-2000; Arabischer Einwanderer; Peronismus; Argentinien; Arabs / Political activity / Argentina / History / 20th century; Peronism / History / 20th century; Arabes / Activité politique / Argentine / Histoire / 20e siècle; Péronisme / Histoire / 20e siècle; Arabs / Political activity; Peronism; Argentina; 1900-1999; History